Jerusalem and Other Holy Places as Foci of Multireligious and Ideological Confrontation - Hartog, Pieter B.; Wieringen, Archibald L.H.M. van; Tohar, Vered; Laderman, Shulamit (Jewish and Christian Perspectives Series, 2021)
Jerusalem and Other Holy Places as Foci of Multireligious and Ideological Confrontation brings together the papers that were read at an international conference at the Schechter Institute in Jerusalem in May 2018. The contributions to this volume develop a multi-disciplinary perspective on holy places and their development, rhetorical force, and oft-contested nature. Through a particular focus on Jerusalem, this volume demonstrates the variety in the study of holy places, as well as the flexibility of geographic and historical aspects of holiness.